Dark Energy in Spherically Symmetric Universe Coupled with Brans-Dicke Scalar Field - Koijam Manihar Singh; Gauranga C. Samanta (Advances in High Energy Physics)
The phenomenon of dark energy and its manifestations are studied in a spherically symmetric universe considering the Brans-Dicke scalar tensor theory. In the first model, the dark energy behaves like a phantom type and in such a universe the existence of negative time is validated with an indication that our universe started its evolution before t=0. Dark energy prevalent in this universe is found to be more active at times when other types of energies remain passive. The second model of universe begins with big bang. On the other hand, the dark energy prevalent in the third model is found to be of the quintessence type. Here, it is seen that the dark energy triggers the big bang and after that much of the dark energy reduces to dark matter. One peculiarity in such a model is that the scalar field is prevalent eternally; it never tends to zero.